La lexicografía vasca a lo largo de la historia - Karlos Cid Abasolo (Revista de Filología Románica, 2010)
This paper is divided into two parts: the first one deals briefly with the history of Basque lexicography, from its origins (the Emilian Glosses) up to the Basque-Basque dictionary Orotariko Euskal Hiztegia – Diccionario General Vasco, consisting of 16 volumes, finished in 2005. In the second part the most important procedures which the Basque language has, like any other, to create and renew its vocabulary are studied: composition, derivation and borrowing. The latter has been by far the most controversial, due to the secular claim of the alleged purity of Basque on behalf of its defenders, with Larramendi as their front man. This purist sector, by no means a minority in the history of the Basque language, has denied Basque the use of linguistic loans (including, of course, vocabulary), has chosen a different way (neologisms based on composition or derivation) for the coining of new concepts and, what is more critical, for the expression of existing concepts for which Basque already had words borrowed from other languages. Modern Basque Lexicography has proven successful in overcoming these prejudices and in collecting and analysing the Basque vocabulary without ignoring one of its definitory features (loanwords), as Basque has traditionally been a language that has always lived in contact with other languages.